![image](https://tex.z-dn.net/?f=12-x%5E2-x%5Cgeq0+%5C+%5Cwedge+%5C+x%2B3%3E0%0A%5C%5C%0A%5C%5Cx%5E2%2Bx-12%5Cleq0+%5C+%5Cwedge+%5C+x%3E-3%0A%5C%5C%0A%5C%5Cx%5E2%2B4x-3x-12%5Cleq0%0A%5C%5C%0A%5C%5Cx%28x%2B4%29-3%28x%2B4%29%5Cleq0%0A%5C%5C%0A%5C%5C%28x%2B4%29%28x-3%29%5Cleq0%0A%5C%5C%0A%5C%5CX%3D%5C%7B%5B-4%2C3%5D%5Ccap%28-3%2C%2B%5Cinfty%29%5C%7D%0A%5C%5C%0A%5C%5CX%3D%28-3%2C3%5D)
0
\\
\\x^2+x-12\leq0 \ \wedge \ x>-3
\\
\\x^2+4x-3x-12\leq0
\\
\\x(x+4)-3(x+4)\leq0
\\
\\(x+4)(x-3)\leq0
\\
\\X=\{[-4,3]\cap(-3,+\infty)\}
\\
\\X=(-3,3]" alt="12-x^2-x\geq0 \ \wedge \ x+3>0
\\
\\x^2+x-12\leq0 \ \wedge \ x>-3
\\
\\x^2+4x-3x-12\leq0
\\
\\x(x+4)-3(x+4)\leq0
\\
\\(x+4)(x-3)\leq0
\\
\\X=\{[-4,3]\cap(-3,+\infty)\}
\\
\\X=(-3,3]" align="absmiddle" class="latex-formula">